Pandangan Harald Motzki tentang Evolusi Tradisi Hadis: Antara Fakta Sejarah dan Proses Legitimasi - Moh Akib Muslim; Avanda Chintya; M Kholisul Iman (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
This article examines Harald Motzki's views on the evolution of the hadith tradition, focusing on the relationship between historical facts and the process of legitimization in the transmission of hadiths. The primary objective of this research is to analyze how hadiths, accepted as authentic and authoritative, undergo a process of formation and legitimization in the historical context of Islam. The methodology used is a critical analysis of Motzki's works, examining how he addresses issues of the authenticity of the sanad and matan of hadiths, as well as how these hadiths developed and were accepted within the Muslim community. The research findings show that Motzki emphasizes the importance of historical context in evaluating the authority of hadiths and critiques traditional understandings of hadith validity. He also highlights how the processes of legitimization and the formation of hadiths are linked to political and social factors in early Islam. In conclusion, this article suggests that to fully understand the evolution of the hadith tradition, a deeper examination of the social and political factors influencing the formation and acceptance of hadiths is necessary. This approach is important for providing new insights into contemporary hadith studies.